PENGARUH KOMPETENSI PEJABAT PENATAUSAHAAN KEUANGAN, PENGAWASAN KEUANGAN DAERAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH ( Studi Empiris Pada SKPD Kabupaten Kampar ) - Pakar Firdaus; Andreas '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The research purpose is for testing empirically effect of the competence financial administration officials, the local financial monitoring and information technology utilization to the value of local government financial reporting information on SKPD in Kampar district. The analytical method used is that in the multiple regression t test to see the effect of each independent variable on the dependent variable. This research uses primary data by distributing questionnaires to a sample of 102 people from Echelon 2 and 3 at SKPD Kampar District Government. Based on the analysis, it is known that the independent variables that have an influence on the information value of local government financial reporting information is competence of the financial administration officials, local financial monitoring and information technology utilization. The coefficient determination of this research is 13.6%, while 86.4% explained by other variables not included in this research model.Keyword : information value, financial administration officials competence, local financial monitoring and information technology utilization.